Reformulasi Living Law dalam Kitab Undang-Undang Hukum Pidana dan Tantangannya terhadap Asas Legalitas - Haris Habibi; Ismaidar Ismaidar; Abdul Rahman Maulana Siregar; Khairuddin Siregar; Jhoni Muda Pratama Barus; Medi Islamta Sembiring; Doni Sabda Tanjung (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code recognizes living law as part of Indonesia’s criminal justice system through Articles 2, 96, and 597. This reform reflects a significant shift in Indonesia’s criminal law by accommodating legal pluralism and the diverse values existing within society. This study examines the reformulation of living law in the Criminal Code, analyzes the resulting paradigm shift in criminal law, and evaluates its implications for the principle of legality. The research employs a normative legal method using statutory and conceptual approaches. Primary, secondary, and tertiary legal materials were collected through library research and analyzed qualitatively. The findings indicate that the recognition of living law moves Indonesia’s criminal law from a strictly formal legality approach toward a more pluralistic framework by incorporating societal norms into the national legal system. Nevertheless, this recognition raises challenges concerning legal certainty, consistency in the application of criminal law, and the protection of the principle of legality. Therefore, effective implementation requires balancing respect for legal diversity with the need to maintain legal certainty and uphold the fundamental principles of modern criminal law.